2018
DOI: 10.3390/molecules23102469
|View full text |Cite
|
Sign up to set email alerts
|

Measurements, Thermodynamic Modeling, and a Hydrogen Bonding Study on the Solubilities of Metoprolol Succinate in Organic Solvents

Abstract: The solubilities of metoprolol succinate (a cardioselective β1 adrenergic receptor) in methanol, ethanol, n-propanol, isopropanol, n-butanol, ethyl acetate, and acetone were measured at temperatures ranging from (278.2 to 318.2) K using a solid–liquid equilibrium method. The solubility of metoprolol succinate increases with increasing temperature. At a fixed temperature, the solubility decreases in the order methanol > ethanol > n-butanol > n-propanol > isopropanol > acetone > ethyl acetate. The enthalpy of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…These findings revealed that the experimental solubility data for FBX were in good accord with the published values [1,9]. Table 1 summarizes the findings, which show that the solubility of FBX increased considerably with increasing temperature in all mono solvents examined (p < 0.05) and was in good agreement with prior research [16][17][18] (1.14 × 10 −6 ) at 318.2 K. Since PEG-400 has the maximum solubility of FBX compared to the other mono solvents tested, it may be the optimal solvent for FBX solubility.…”
Section: Measured Solubility Data Of Fbxsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings revealed that the experimental solubility data for FBX were in good accord with the published values [1,9]. Table 1 summarizes the findings, which show that the solubility of FBX increased considerably with increasing temperature in all mono solvents examined (p < 0.05) and was in good agreement with prior research [16][17][18] (1.14 × 10 −6 ) at 318.2 K. Since PEG-400 has the maximum solubility of FBX compared to the other mono solvents tested, it may be the optimal solvent for FBX solubility.…”
Section: Measured Solubility Data Of Fbxsupporting
confidence: 87%
“…The obtained suspensions were vortexed for 10 min. All of the samples were shaken at 100 rpm for 72 h in a "WiseBath ® WSB Shaking Water Bath (Model WSB-18/30/-45, Daihan Scientific Co., Ltd., Seoul, Korea)" [16,17]. Each sample was obtained, filtered, and centrifuged at 5000 rpm for 30 min after equilibrium was reached (equilibrium time = 72 h).…”
Section: Fbx Solubility Measurementmentioning
confidence: 99%
“…Comparing the melting enthalpies of pure crystalline MS with that of MS in the filament revealed a reduction in the melting enthalpy from 178.7 to 68.1 J/g (total weight). The melting enthalpy of pure crystalline MS is in agreement with that reported in the literature [ 71 ]. Reduced melting enthalpies in the filament are in part attributable to concentration reduction from 100% in the raw materials to 40% MS and 20% PEG1500 in the filament.…”
Section: Resultssupporting
confidence: 90%
“…The Apelblat model, which is a commonly applied semi-empirical correlation model, , correlates the mole fraction solubility data and the absolute temperature in pure solvents, derived from the Clausius–Clapeyron equation, can be expressed as: where A , B , and C are model parameters of the equation. A and B represent the nonideality of the change of the activity coefficient in the actual solution, while C denotes the effect of temperature on the fusion enthalpy.…”
Section: Thermodynamic and Correlating Modelsmentioning
confidence: 99%